Pulp Therapy of Primary Dentition; its Relevance despite Insufficient Histological Evidence: A Review: Pulp therapy of the primary dentition - Sanusi, Sarliza Yasmin; Al-Batayneh, Ola Barakat (Iranian Endodontic Journal, 2023)
Pulp treatment in primary dentition is generally divided into vital and non-vital pulp therapies and assists in the preservation of pulpally involved primary teeth in the dental arch until the affected tooth naturally exfoliates. The success of pulp therapies depends on several factors; e.g. proper case selection, accurate diagnosis and good coronal seal. To date, studies on the success and failure rates of pulp treatments are based on clinical signs and symptoms, radiographic findings and histological analysis. However, the clinical and radiographic evidence may not completely portray the true status of the dental pulp. Histological evidence remains the gold standard in the assessment of pulp condition, whether it is in a healthy or adverse state. The aims of the current research were to summarise the treatment outcomes of pulp therapy in primary dentition based on clinical, radiographic and histological criteria, and to support its relevance in the presence of limited histological evidence to measure authentic treatment success. An electronic database search of dental literature from 1990 to 2022 was carried out using the MEDLINE, i.e. PubMed, database. Current dental literature showed that the success rates of primary tooth pulp therapy are high. The obtained results were based largely on clinical and radiographic studies with narrow histological investigations to assess the treatment outcome(s) of pulp therapy in primary dentition. Despite the scarcity of histological evidence, pulp therapies in primary teeth are still practical due to their statistically empirical success compared to their failure. Consequently, pulp therapy of primary dentition is still relevant, and should continue to be indicated as an important treatment option.